Perancangan Sistem Informasi Inventory Safety Tools pada PT. Kumpul Mas Abadi - Surtika Ayumida; Ayumida, Surtika; Hakim, Lukmanul; Dewi, Sely Fitria (PROFITABILITAS, 2022)
PT Kumpul Mas Abadi is a company that supplies safety tools. Currently, inventory management is experiencing problems because it is still done manually. The purpose of this study is to design a website-based computerized inventory information system to replace the manual system. The research method used is software development with the Water Fall method. The results showed: First, the design of the inventory information system at PT Kumpul Mas Abadi has been completed using the PHP programming language and the Laravel framework; Second, the design of information systems using the Waterfall Method consists of three stages, namely system design, software design, and implementation design; Third, the implementation of a website-based information system needs to be implemented immediately so that companies get various benefits, namely inventory management becomes more effective and efficient which in turn can support increased productivity and company performance.